Research Trends: Argument Driven Inquiry (ADI) Model in Science Learning - Anggita Meilina Putri; Endang Purwaningsih; Purbo Suwasono; Muhammad Ikhbar Ihsan; Monika Ruth Cahayana; Kafa Pramitha Anggraini Indhira Artanti (Postgraduate, University of Mataram, 2026)
This study aims to analyze research trends regarding the Argument-Driven Inquiry (ADI) model in science education. A Systematic Literature Review (SLR) was conducted using the Scopus database, following PRISMA 2020 guidelines. From an initial 20 records identified, 11 high quality original articles published between 2019 and 2025 met the strict inclusion criteria. The findings indicate that while publication numbers appear to fluctuate, this is largely attributed to ongoing data indexing for the year 2025 rather than a decline in academic interest. The ADI model is most frequently implemented at the secondary school level, particularly in Physics and Chemistry. Results demonstrate that ADI significantly enhances scientific argumentation, conceptual mastery, and critical thinking. Furthermore, technical modifications such as rADI and MADI have proven effective in addressing diverse student needs and classroom constraints. In conclusion, ADI serves as a robust framework for 21st-century science learning, though future research must prioritize long-term sustainability studies and teacher professional development to ensure successful implementation across broader educational contexts.